2020
DOI: 10.3390/ijerph17249390
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Nitrate Content in Groundwater and Evaluation of Potential Health Risks: A Case Study of Rural Areas in Northern China

Abstract: Nitrate pollution is considered to be one of the most common environmental problems in groundwater, especially in areas affected by human mining, such as the arid region of northern China. However, the human health risk assessment of nitrate pollution in this area has not yet been carried out. In this study, groundwater samples were taken in the Selian mining area in Inner Mongolia to conduct a full analysis of water quality. On this basis, the groundwater quality, the distribution range of nitrate pollution, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…A study conducted by [41] revealed the impact of NO 3 − contamination of over 50 mg/L from one mine that was detected in water supplied to a village situated close to a mine in the Limpopo province of South Africa. Groundwater sampled around the Selian mining area in China revealed a maximum NO 3 − concentration of 109 mg/L, which is alarmingly higher than the global acceptable 10 mg/L limit [22]. Most South African mines use ammonium-based explosives, although less data is available on water quality contaminated with NO 3 − from explosives used during mining.…”
Section: Nitrate Contamination From Mining Activitiesmentioning
confidence: 96%
See 2 more Smart Citations
“…A study conducted by [41] revealed the impact of NO 3 − contamination of over 50 mg/L from one mine that was detected in water supplied to a village situated close to a mine in the Limpopo province of South Africa. Groundwater sampled around the Selian mining area in China revealed a maximum NO 3 − concentration of 109 mg/L, which is alarmingly higher than the global acceptable 10 mg/L limit [22]. Most South African mines use ammonium-based explosives, although less data is available on water quality contaminated with NO 3 − from explosives used during mining.…”
Section: Nitrate Contamination From Mining Activitiesmentioning
confidence: 96%
“…− concentration [87,88]. During mining, tailings that are transported to the surface from the pits are piled next to the mine, where the residual explosives are washed off and dissolve in rain water, which eventually flows into nearby streams and rivers, resulting in elevated NO 3 − concentrations [9,19,22]. Mine wastewater remediation strategies tend to focus on metal and SO 4 2− remediation due to their known toxicity and lethality, while NO 3 − remediation garners less focus.…”
Section: Nitrate Contamination From Mining Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It not only helps to improve rural residents' participation in environmental pollution control but also helps to weaken social contradictions and promote the healthy development of rural environmental pollution control [9]. However, from the perspective of administrative management, rural environmental pollution control still faces some difficulties, such as unclear legal responsibility of administrative subjects, single relief methods for administrative damage, small scope of application of administrative management, and lack administrative procedures [10]. In this regard, to give full play to administrative management in rural environmental pollution control, all regions also need to clarify the legal responsibilities of administrative subjects and expand administrative damage relief methods and scientific design procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to perchlorate exposure, one of a major source of nitrate intake is from drinking water [8]. Generally, nitrate does not directly affect the human body, but when converted into nitrite in the digestive tract, it can induce certain diseases, such as cancer [9]. In addition, de ciency of trace elements and microbial contamination in drinking water could also affect the occurrence of EC and GC [10][11][12].…”
mentioning
confidence: 99%